1015. Enhanced Detection of Bloodstream Pathogens From Positive Blood Culture Specimens With an Improved Multiplex PCR Molecular Diagnostic System. (26th November 2018) - Green, Jeremy; Carter, Caitlin; Chandler, Craig; Clark, Angela; Thatcher, Stephanie
Abstract: Background: Timely bloodstream infection (BSI) pathogen identification requires robust sample purification and testing methods that can accommodate the wide variety of blood culture media used for growing positive blood culture (PBC) specimens. Sensitive molecular methods are needed for identification of all organisms present in PBD, especially polymicrobial cultures which can be difficult to identify with standard methods. Multiple types of BD and BioMérieux blood culture media commonly used in hospital laboratories were used to evaluate the performance of a prototype BioFire® FilmArray® Blood Culture Identification 2 (BCID2) Panel with PBCs. Methods: Fungi (seven) and bacteria (19) were independently seeded in blood samples, inoculated into as many as eight different types of blood culture bottles, and incubated on the recommended instrument. Time to positivity (TTP) was recorded for all PBCs. Subsets of PBCs were enumerated and tested on the BioFire BCID2 Panel and BioFire® FilmArray® Blood Culture Identification (BCID) panel. Polymicrobial testing was performed by seeding fast and slow growing organisms into the same bottles. Results: Over 750 PBCs were enumerated; ~500 PBCs were tested on the BioFire BCID2, and over 200 were also tested on the BioFire BCID. 100% of seeded PBCs tested on the BioFire Panels resulted in correct pathogen identification. Across all bottle types, fungi grew to levels ranging from 8E+05 to 5E+07 CFU/mL, Gram-positive bacteria titers ranged from 7E+06 to 2E+09, and Gram-negative bacteria titers ranged from 9E+07 to 3E+09. Polymicrobial PBCs (30) had reduced titers of slow growing organisms when seeded with fast growing organisms but were detected by both BioFire BCID Panels at a rate of 99%. Conclusion: This study demonstrates that a prototype BioFire BCID2 Panel, and the BioFire BCID Panel, robustly detect and identify (100%) BSI pathogens over a multitude of common blood culture media and systems. Results confirm PBC (single and polymicrobial) titers are above the levels of sensitivity for both BioFire panels. An expanded menu of targets (organism and resistance) and faster run time with the BioFire BCID2 Panel will offer a flexible and comprehensive aid in the diagnosis of BSIs. The BioFire® BCID2 Panel has not yet been evaluated by the FDA or other regulatory agencies for in vitro diagnostic use. Disclosures: J. Green, BioFire Diagnostics, LLC: Employee, Salary. C. Carter, BioFire Diagnostics, LLC: Employee, Salary. C. Chandler, BioFire Diagnostics, LLC: Employee, Salary. A. Clark, BioFire Diagnostics, LLC: Employee, Salary. S. Thatcher, BioFire Diagnostics, LLC: Employee, Salary.